Carbon composite titanium / fluorine double-doped composite sodium ferric phosphate composite material as well as preparation method and application thereof

By introducing titanium/fluorine double-doping and spray granulation processes into NFPP, carbon composite titanium/fluorine double-doping composite sodium phosphate material with a porous bowl structure was prepared, which solved the problem of insufficient conductivity and cyclic stability of NFPP, and achieved efficient improvement in the performance of the positive electrode material of sodium ion battery.

CN119560523APending Publication Date: 2025-03-04武汉启钠新能源科技有限公司 +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411583834.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing sodium ion battery cathode material composite sodium ferric phosphate (NFPP) has insufficient conductivity and cyclic stability, resulting in its limitations in industrial applications.

Method used

The carbon composite titanium/fluorine double-doping strategy was adopted, and the carbon composite titanium/fluorine double-doping composite sodium phosphate material with a porous bowl-like structure was prepared to effectively inhibit the formation of NaFePO4 heterophase.

Benefits of technology

It significantly improves the intrinsic conductivity and cyclic stability of NFPP, enhances its rate performance and long cycle stability, and is suitable for industrial production and applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005123815610000011
    Figure HDA0005123815610000011
  • Figure HDA0005123815610000012
    Figure HDA0005123815610000012
  • Figure HDA0005123815610000021
    Figure HDA0005123815610000021
Patent Text Reader

Abstract

The invention discloses a carbon composite titanium / fluorine double-doped composite sodium ferric phosphate composite material, the stoichiometric formula of which is Na < 4 > Fe < 3-2x > Ti < x > (PO4) < 2-y > F < 3 > y P < 2 > O < 7 > / C, xlt; 0 lt, 0.04, 0 lt; yt; Yt; 0.2 part; and the hollow bowl-shaped porous structure is formed. According to the invention, the intrinsic conductivity of the NFPP can be effectively improved, the problem of impurity phase of NaFePO4 can be controlled, and the gram capacity of the NFPP can be improved; when the carbon composite titanium / fluorine double-doped composite sodium ferric phosphate composite material is used as a sodium ion battery positive electrode material, relatively good rate capability, long cycle stability and the like can be shown; and the related preparation cost is low, the method is environment-friendly, and industrial application is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemical energy materials, and specifically relates to a carbon-composite titanium / fluorine dual-doped composite sodium iron phosphate composite material and a preparation method and application thereof. Background Art

[0002] The development of efficient energy storage systems is an inevitable requirement for the rapid development of electronic devices and electric vehicles. The scarcity of lithium resources urgently requires the development of new energy storage technologies to make up for this shortcoming. Sodium-ion batteries are considered to be the best supplement to lithium-ion batteries due to their abundant reserves. However, the large ionic radius of sodium ions leads to problems such as low ion migration rate, slow reaction kinetics, low theoretical specific capacity and short cycle period, which seriously limits its industrial application. The development of sodium-ion battery cathode materials with high theoretical specific capacity and excellent cycle performance and the transformation from laboratory to industrial production are current research hotspots.

[0003] At present, the positive electrode materials of sodium ion batteries are mainly divided into three types: polyanion type, Prussian blue type and layered oxide type. Layered oxide positive electrode materials have a high theoretical reversible capacity, but they have strong covalent properties, there are multiphase transitions during the electrochemical reaction, poor cycle stability, low redox potential, and are extremely sensitive to humid environments. Prussian blue materials have an open large framework to accommodate sodium ions and can reversibly insert / remove two sodiums at a high rate, but because of its production method, it will produce a large number of lattice defects and coordinated water, which affect the activity of sodium ion storage sites, and the yield is low and the thermal stability is poor, making it difficult to carry out large-scale production and practical application. In contrast, polyanions The iron-based phosphate material with a three-dimensional open framework structure has a crystal structure that can support and stabilize the material, Na + The advantages of small volume change (≈4%) ​​during insertion / removal, long stable cycling at high rates, relatively high operating voltage, low cost, environmentally friendly production process, and applica- tion for large-scale production have won the favor of many researchers.

[0004] Composite sodium iron phosphate (NFPP) has high electrochemical stability, crystal structure stability, and high theoretical specific capacity (129 mAh g -1 ) and low cost have attracted widespread attention. However, its low conductivity and the easy formation of NaFePO 4Impurities are formed, resulting in a decrease in its high-rate performance and low utilization rate of raw materials, which seriously limits its industrial development. Currently, the conductivity of NFPP is mainly improved by means of carbon coating through nanosizing. However, this method is only limited to the surface modification of nanomaterials, and the conductivity of the material itself has not been fundamentally improved. The low conductivity of NFPP requires an increase in the carbon content during the preparation process to enhance the conductivity. The increase in carbon content will reduce the overall tap density of the material, which is not conducive to the application of industrial energy storage devices. How to enhance the intrinsic conductivity of the material (reduce the demand for high carbon content) is a technical difficulty in maximizing the commercial value of NFPP. The introduction of ion doping will interact with adjacent atoms, causing changes in the local electronic structure, which is considered an effective means to improve the conductivity of materials. However, during the preparation process of NFPP, the formation of 4 impurities is difficult to control. Finding an effective preparation method to suppress the formation of NaFePO 4 remains a difficulty in the preparation process of NFPP. Summary of the Invention

[0005] The main purpose of the present invention is to provide a carbon composite titanium / fluorine double-doped sodium iron phosphate composite cathode material, which can effectively improve the intrinsic conductivity of NFPP, control problems such as NaFePO 4 impurities, increase the specific capacity of NFPP, and then significantly improve the rate performance and long-cycle stability of the obtained NFPP-based cathode material; and the involved preparation method is relatively simple and environmentally friendly, suitable for popularization and application.

[0006] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0007] A carbon composite titanium / fluorine double-doped sodium iron phosphate composite material, with a chemical formula of Na 4 Fe 3-2x Ti x (PO 4 ) 2-y F 3y P 2 O 7 / C, where 0 < x < 0.04 and 0 < y < 0.2; the composite material has a porous bowl-shaped hollow structure.

[0008] Further, in the carbon composite titanium / fluorine double-doped sodium iron phosphate composite material, the carbon content is 1-5% (wt%), the specific surface area is 5-15 m 2 / g, and the pore size distribution range is 10-100 nm.

[0009] Further, the particle size of the carbon composite titanium / fluorine double-doped sodium iron phosphate composite material is 0.2-10 μm.

[0010] The preparation method of the above carbon composite titanium / fluorine double-doped sodium iron phosphate composite material comprises the following steps:

[0011] S1. Prepare the raw material dispersion: According to the chemical formula Na 4 Fe 3-2x Ti x (PO 4 ) 2-y F 3y P 2 O 7 Weigh the raw materials, and disperse the weighed carbon source, phosphorus source, sodium source, iron source, titanium source and fluorine source in water according to a ratio;

[0012] S2. Refine the particles in the dispersion: Place the dispersion obtained in S1 in a ball mill and a sand mill in sequence to refine the raw material particles;

[0013] S3. Prepare the precursor material: Spray granulate the dispersion obtained in S2 to obtain the sodium iron phosphate composite precursor material;

[0014] S4. Prepare the carbon composite titanium / fluorine double-doped sodium iron phosphate composite material: Calcinate the sodium iron phosphate composite precursor obtained in S3 at a high temperature in a protective atmosphere, and then crush it to obtain the carbon composite titanium / fluorine double-doped sodium iron phosphate composite material.

[0015] In the above solution, the specific steps for preparing the raw material dispersion in S1 are as follows: Under the conditions of oil bath and stirring, add the iron source, sodium source, phosphorus source, titanium source, fluorine source and carbon source to water, and continue stirring to fully dissolve and disperse the raw materials to prepare the raw material dispersion.

[0016] In the above solution, the oil bath temperature is 60-90 °C.

[0017] In the above solution, in S1, the molar ratio of the sodium source, iron source, phosphorus source, titanium source and fluorine source is 4:3-2x:2-y:x:3y (where 0 < x < 0.05, 0 < y < 0.2); the addition amount of the carbon source is 5-15% of the theoretical mass of the NFPP product of the raw materials (the designed mass of the product of Na 4 Fe 3-2x Ti x (PO 4 ) 2-y F 3y P 2 O 7 product).

[0018] Furthermore, in S2, the ball milling time is 3-8 h, and the ball milling speed is 300-500 r / min; the sand milling time is 2-6 h, and the sand milling speed is 1000-3000 r / min.

[0019] In the above scheme, the sodium salt can be selected from at least one of sodium carbonate, disodium bicarbonate, sodium dihydrogen carbonate, sodium pyrophosphate, sodium chloride, sodium nitrate, sodium sulfate, sodium thiosulfate, sodium fluoride, etc.

[0020] In the above scheme, the iron salt can be selected from at least one of ferrous sulfate heptahydrate, ferric nitrate nonahydrate, ferrocene, ferric sulfate, ferric phosphate, ferrous phosphate, ferric citrate, ferric oxalate, ferric chloride hexahydrate, ferric acetylacetonate, and the like.

[0021] In the above scheme, the phosphorus source can be selected from at least one of phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate.

[0022] In the above scheme, the titanium source can be selected from at least one of isopropyl titanate, tetraethyl titanate, tetrabutyl titanate, nano titanium oxide, titanium trichloride, titanium tetrafluoride and the like.

[0023] In the above scheme, the fluorine source can be selected from at least one of ammonium fluoride, hydrofluoric acid, sodium fluoride, etc.

[0024] In the above scheme, the carbon source is at least one of glucose, sucrose, polyvinyl pyrrolidone, citric acid, dopamine hydrochloride, polyethylene glycol, etc.

[0025] In the above scheme, in S3, the inlet air temperature of the spray drying is 150-230°C, the outlet air temperature is 80-120°C, the feed rate is 7-14mL / min, and the inlet pressure is 0.1-0.4MPa.

[0026] Further, in S4, the calcination equipment is a tubular furnace; the protective atmosphere is Ar, N 2 、Ar / H 2 or N 2 / H 2 .

[0027] The calcination is carried out in one step, with a heating rate of 2-5°C / min, a calcination temperature of 400-600°C, and a calcination time of 6-12h.

[0028] Application of the carbon-composite titanium / fluorine dual-doped composite sodium iron phosphate composite material obtained by the above preparation method in the positive electrode of a sodium ion battery.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The present invention adopts a titanium / fluorine dual doping strategy, which can effectively inhibit the NaFePO 4 The generation of NFPP can be improved, and the generation rate of NFPP can be increased, effectively increasing the gram capacity of NFPP;

[0031] (2) The present invention adopts cationic and cation-dual ion doping combined with spray granulation and calcination process, which can effectively change the electron density inside the material and enhance the NFPP cycle stability while regulating the microstructure of the composite material, so that the NFPP can achieve excellent electrochemical performance;

[0032] (3) The hollow bowl-shaped structure of the prepared NFPP is conducive to the rapid penetration of electrolyte and the rapid transport of ions;

[0033] (4) The raw materials involved in the present invention are cheap and easily available. The obtained sodium ion positive electrode material is green and environmentally friendly during the preparation process, has no pollution emissions, and can be mass-produced, which is conducive to industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 (a) low magnification and (b) high magnification scanning electron microscope images of the carbon-composite titanium / fluorine dual-doped composite sodium iron phosphate prepared in Example 1 of the present invention.

[0035] Figure 2 X-ray diffraction pattern of the carbon-composite titanium / fluorine dual-doped composite sodium iron phosphate prepared in Example 1 of the present invention.

[0036] Figure 3 This is a comparison chart of the rate performance of the composite materials prepared in Example 1 of the present invention and Comparative Examples 1, 2, 3, and 4 for use as positive electrode materials for sodium ion batteries.

[0037] Figure 4 This is a comparison chart of the long cycle stability of the composite materials prepared in Example 1 of the present invention and Comparative Examples 1, 2, 3, and 4 for use as positive electrode materials for sodium ion batteries. DETAILED DESCRIPTION

[0038] The technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention and the comparative examples. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. Unless otherwise specified, the equipment and reagents used in the present invention are conventional commercial products in the art.

[0039] Example 1

[0040] A carbon-composite titanium / fluorine dual-doped composite sodium iron phosphate, the preparation method of which comprises the following steps:

[0041] S1. Prepare a raw material dispersion: add 55 mL of pure water to a beaker and heat it to 70° C. in an oil bath, then add 22.4 g of ammonium dihydrogen phosphate and stir to dissolve, take 53.6 g of ferrous oxalate dihydrate and add it and stir vigorously, after the solution is uniform, add 26.6 g of sodium pyrophosphate, after it is evenly dispersed, add 0.284 g of isopropyl titanate, 0.56 g of ammonium fluoride, and 6.2 g of sucrose in sequence, and continue stirring for 30 min to make the dispersion reach a uniform state;

[0042] S2, fineness of particles in the dispersion: the dispersion in S1 was placed in a grinding jar, loaded into a planetary ball mill and ball-milled at a speed of 400 r / min for 4 h, then taken out and transferred to a sand mill and sand-milled at a speed of 1000 r / min for 4 h, and the dispersion was collected;

[0043] S3, preparing precursor materials: spray granulation of the dispersion obtained in S2 by spray drying, controlling the air inlet temperature at 180°C, the feed rate at 14 mL / min, and the spray atmosphere as air, to finally obtain a precursor dry powder;

[0044] S4, preparation of carbon-composite titanium / fluorine dual-doped composite sodium iron phosphate composite material: the composite sodium iron phosphate precursor obtained in S3 is placed in a crucible under N 2 Under protective conditions, the temperature was raised to 550°C at a rate of 4°C / min and calcined for 10 h to obtain a carbon-composite titanium / fluorine-doped sodium iron phosphate composite material (denoted as Na 4 Fe 2.98 Ti 0.01 (PO 4 ) 1.95 F 0.15 P 2 O 7 / C).

[0045] Example 2

[0046] A carbon-composite titanium / fluorine dual-doped composite sodium iron phosphate, the preparation method of which comprises the following steps:

[0047] S1. Prepare a raw material dispersion: add 55 mL of pure water to a beaker and heat it to 60°C in an oil bath, then add 30.16 g of ferrous phosphate and stir to disperse, take 17.27 g of ferrous oxalate dihydrate and add it and stir vigorously, after the solution is evenly dispersed, add 23.4 g of disodium hydrogen phosphate, 0.53 g of sodium carbonate, and 10 mL of water, after it is evenly dispersed, add 0.16 g of nano titanium dioxide, 0.56 g of ammonium fluoride, and 7.45 g of glucose in sequence, and continue stirring for 30 min to make the dispersion reach a uniform state;

[0048] S2, fineness of particles in the dispersion: the dispersion in S1 was placed in a grinding jar, loaded into a planetary ball mill and ball-milled at a speed of 380 r / min for five hours, then taken out and transferred to a sand mill and sand-milled at 1500 r / min for 2 hours, and the dispersion was collected;

[0049] S3, preparing precursor materials: spray granulation of the dispersion obtained in S2 by spray drying, controlling the air inlet temperature at 190°C, the feed rate at 10 mL / min, and the spray atmosphere as air, to finally obtain a precursor dry powder;

[0050] S4. Preparation of carbon-composite titanium / fluorine-doped composite sodium iron phosphate composite material: The composite sodium iron phosphate precursor obtained in S3 is placed in a crucible under Ar / H 2 Under protective atmosphere conditions, the temperature was raised to 500°C at a rate of 3°C / min and calcined for 10 hours to obtain a carbon-composite titanium / fluorine dual-doped composite sodium iron phosphate composite material.

[0051] Example 3

[0052] A carbon-composite titanium / fluorine dual-doped composite sodium iron phosphate, the preparation method of which comprises the following steps:

[0053] S1. Prepare a raw material dispersion: add 55 mL of pure water to a beaker and heat it to 80° C. in an oil bath, then add 44.95 g of ferrous oxalate dihydrate and stir vigorously. After the solution is evenly dispersed, add 10.58 g of diammonium hydrogen phosphate and 21.12 g of sodium carbonate. After the solution is evenly dispersed, add 0.228 g of tetraethyl titanate, 1.11 g of ammonium fluoride, and 4.96 g of citric acid in sequence, and continue stirring for 30 min to make the dispersion reach a uniform state;

[0054] S2, fineness of particles in the dispersion: the dispersion in S1 was placed in a grinding jar, loaded into a planetary ball mill and ball-milled at a speed of 450 r / min for three hours, then taken out and transferred to a sand mill and sand-milled at a condition of 1500 r / min for 2 hours, and the dispersion was collected;

[0055] S3, preparing precursor materials: spray granulation of the dispersion obtained in S2 by spray drying, controlling the air inlet temperature at 190°C, the feed rate at 18 mL / min, and the spray atmosphere as air, to finally obtain a precursor dry powder;

[0056] S4, preparation of carbon-composite titanium / fluorine dual-doped composite sodium iron phosphate composite material: the composite sodium iron phosphate precursor obtained in S3 is placed in a crucible under N 2 / H 2 Under protective atmosphere, the temperature was raised to 500°C at a rate of 5°C / min and calcined for 10 hours to obtain a carbon-composite titanium / fluorine-doped composite sodium iron phosphate composite material.

[0057] Comparative Example 1

[0058] A carbon-composite titanium-doped composite sodium iron phosphate, the preparation method of which comprises the following steps:

[0059] S1. Prepare a raw material dispersion: add 55 mL of pure water to a beaker and heat it to 70° C. in an oil bath, then add 23 g of ammonium dihydrogen phosphate and stir to dissolve, add 53.61 g of ferrous oxalate dihydrate and stir vigorously, and after the solution is uniform, add 26.6 g of sodium pyrophosphate, and after the dispersion is uniform, add 0.284 g of isopropyl titanate and 6.21 g of sucrose in sequence, and continue stirring for 30 min to make the dispersion uniform;

[0060] S2, fineness of particles in the dispersion: the dispersion in S1 was placed in a grinding jar, loaded into a planetary ball mill and ball-milled at a speed of 400 r / min for 4 h, then taken out and transferred to a sand mill and sand-milled at a speed of 1000 r / min for 4 h, and the dispersion was collected;

[0061] S3, preparing precursor materials: spray granulation of the dispersion obtained in S2 by spray drying, controlling the air inlet temperature at 180°C, the feed rate at 14 mL / min, and the spray atmosphere as air, to finally obtain a precursor dry powder;

[0062] S4. Preparation of carbon-composite titanium-doped composite sodium iron phosphate composite material: placing the composite sodium iron phosphate precursor obtained in S3 in a crucible, heating to 550° C. at a rate of 4° C. / min and calcining for 10 h under N2 protection conditions; obtaining a carbon-composite titanium / fluorine dual-doped composite sodium iron phosphate composite material.

[0063] Comparative Example 2

[0064] A carbon-composite fluorine-doped composite sodium iron phosphate, the preparation method of which comprises the following steps:

[0065] S1. Prepare a raw material dispersion: add 55 mL of pure water to a beaker and heat it to 70° C. in an oil bath, then add 53.97 g of ferrous oxalate dihydrate and stir vigorously. After the solution is uniform, add 23.39 g of sodium dihydrogen phosphate, 0.53 g of sodium carbonate, and 23 g of ammonium dihydrogen phosphate. After the dispersion is uniform, add 0.56 g of ammonium fluoride and 6.15 g of sucrose, and continue stirring for 30 min to make the dispersion uniform.

[0066] S2, fineness of particles in the dispersion: the dispersion in S1 was placed in a grinding jar, loaded into a planetary ball mill and ball-milled at a speed of 400 r / min for 4 h, then taken out and transferred to a sand mill and sand-milled at a speed of 1000 r / min for 4 h, and the dispersion was collected;

[0067] S3, preparing precursor materials: spray granulation of the dispersion obtained in S2 by spray drying, controlling the air inlet temperature at 180°C, the feed rate at 14 mL / min, and the spray atmosphere as air, to finally obtain a precursor dry powder;

[0068] S4, preparation of carbon-composite fluorine-doped composite sodium iron phosphate composite material: the composite sodium iron phosphate precursor obtained in S3 is placed in a crucible under N 2 Under protective conditions, the temperature was raised to 550°C at a rate of 3°C / min and calcined for 10 hours to obtain a carbon-composite titanium / fluorine dual-doped composite sodium iron phosphate composite material.

[0069] Comparative Example 3

[0070] A carbon-composite molybdenum-doped composite sodium iron phosphate, the preparation method of which comprises the following steps:

[0071] S1. Prepare a raw material dispersion: add 55 mL of pure water to a beaker and heat it to 70° C. in an oil bath, then add 52.89 g of ferrous oxalate dihydrate and stir vigorously. After the solution is uniform, add 26.6 g of sodium pyrophosphate, 23 g of ammonium dihydrogen phosphate, 0.14 g of molybdenum trioxide, and after the dispersion is uniform, add 6.2 g of sucrose and continue stirring for 30 min to make the dispersion uniform.

[0072] S2, fineness of particles in the dispersion: the dispersion in S1 was placed in a grinding jar, loaded into a planetary ball mill and ball-milled at a speed of 400 r / min for four hours, then taken out and transferred to a sand mill and sand-milled at a condition of 1000 r / min for 4 hours, and the dispersion was collected;

[0073] S3, preparing precursor materials: spray granulation of the dispersion obtained in S2 by spray drying, controlling the air inlet temperature at 180°C, the feed rate at 14 mL / min, and the spray atmosphere as air, to finally obtain a precursor dry powder;

[0074] S4, preparation of carbon-composite molybdenum-doped composite sodium iron phosphate composite material: the composite sodium iron phosphate precursor obtained in S3 is placed in a crucible under N 2 Under protective conditions, the temperature was raised to 550°C at a rate of 5°C / min and calcined for 10 hours to obtain a carbon-composite molybdenum / fluorine dual-doped composite sodium iron phosphate composite material.

[0075] Comparative Example 4

[0076] A carbon-composite titanium / fluorine dual-doped composite sodium iron phosphate, the preparation method of which comprises the following steps:

[0077] S1. Prepare the raw material solution: add 55 mL of pure water to a beaker and heat it to 60°C in an oil bath, then add 120.39 g of ferric nitrate nonahydrate and stir vigorously. After the solution is evenly dispersed, add 56.784 g of sodium dihydrogen phosphate. After the solution is evenly dispersed, add 0.34 g of tetrabutyl titanate, 0.56 g of ammonium fluoride, and 6.24 g of glucose in sequence, and continue stirring for 30 min to make the dispersion reach a uniform state;

[0078] S2, solution gelation and drying: Place the dispersion in S1 on a heated stirrer, raise the temperature to 80°C while stirring continuously, and continue stirring until the water evaporates to form a gel state; then transfer to a 100°C forced air drying oven to completely evaporate the remaining water;

[0079] S3, preparation of carbon-composite titanium / fluorine dual-doped composite sodium iron phosphate composite material: the dried composite sodium iron phosphate precursor powder obtained in S2 is placed in a crucible under N 2 / H 2 Under protective atmosphere conditions, the temperature was raised to 500°C at a rate of 5°C / min and calcined for 10 hours to obtain a carbon-composite titanium / fluorine dual-doped composite sodium iron phosphate composite material.

[0080] The difference between Comparative Examples 1, 2, and 3 and Example 1 is that Comparative Example 1 is only titanium doped, Comparative Example 2 is only fluorine doped, Comparative Example 3 is a molybdenum doped comparative example, and Comparative Example 4 adopts the sol-gel method.

[0081] The carbon-composite titanium / fluorine dual-doped composite sodium iron phosphate prepared in Example 1 was observed for morphology, and the scanning electron microscope results are as follows: Figure 1 As shown by Figure 1 It can be seen that the obtained product has a hollow bowl-shaped porous structure. After testing, its carbon content is 1.45wt% and its specific surface area is 6.17m 2 / g, and the pore size distribution range is 10-90nm.

[0082] The crystal structure of the carbon-composite titanium / fluorine-doped composite sodium iron phosphate composite material prepared in Example 1 and Comparative Examples 1, 2, 3, and 4 was tested, and the X-ray diffraction results are as follows: Figure 2 As shown, it can be seen that the diffraction peaks of the product obtained by the present invention are similar to those of NaCo 3 (PO 4 ) 2 P 2 O 7 Standard card (NFPP phase currently corresponds to NaCo 3 (PO 4 ) 2 P 2 O 7 The diffraction peaks of the standard card are consistent; in addition, Figure 2It can be seen from the circled marks that the products obtained in Comparative Examples 3 and 4 show obvious NaFePO 4 Diffraction peaks, NaFePO in the products obtained in Comparative Example 1 and Comparative Example 2 4 Although the diffraction peaks show a weakening trend, there is a more obvious NaFePO 4 Mixed phase problem.

[0083] The composite materials prepared in Example 1 and Comparative Examples 1, 2, 3, and 4 were respectively used as positive electrode materials to assemble sodium ion batteries, and the steps are as follows:

[0084] The composite material, super P and polyvinylidene fluoride (PVDF) were fully mixed and dispersed in N-methyl-2-pyrrolidone (NMP) in a mass ratio of 8:1:1 to form a uniform slurry. The obtained slurry was then evenly coated on aluminum foil to make an electrode. The electrode was dried in a vacuum drying oven at 120 degrees and cut into electrode sheets with a diameter of 10 mm for later use.

[0085] Using 1.0M NaPF 6 In PC (propylene carbonate) as the electrolyte, glass fiber membrane (Whatman GF / D) as the diaphragm, and metallic sodium as the counter electrode, a sodium ion battery was assembled in an argon-filled glove box in the order of: negative electrode metal shell → sodium metal sheet → diaphragm → positive electrode → gasket → spring → metal positive electrode shell.

[0086] According to the above method, a carbon-composite titanium / fluorine dual-doped composite sodium iron phosphate composite sodium ion battery assembled using the composite material of Example 1 as the positive electrode material, and a composite sodium ion battery assembled using the composite materials of Comparative Examples 1, 2, 3, and 4 as the positive electrode material were obtained respectively.

[0087] Figure 3 The performance comparison diagram of the composite materials prepared in Example 1 of the present invention and Comparative Examples 1, 2, 3, and 4 for the positive electrode of a sodium ion battery in the voltage range of 1.7 to 4.2 V at different current densities is shown in the figure. It can be clearly seen that the carbon-composite titanium / fluorine-doped composite sodium iron phosphate composite sodium ion battery positive electrode material prepared in Example 1 has better rate performance than the composite sodium ion battery negative electrode materials prepared in Comparative Examples 1, 2, 3, and 4. The specific capacity of Example 1 at 1C is 100 mAh g -1 , the specific capacity is 95.8 mAh g at 10C -1 , the specific capacity is 91.8 mAh g at 20C -1 , better than comparative example 1 (98 mAh g -1 , 92.8mAh g -1 and 84mAh g -1 ); Comparative Example 2 (98 mAh g-1 , 90mAh g -1 and 83.9mAh g -1 ); Comparative Example 3 (89 mAhg -1 , 82mAh g -1 and 77.5mAh g -1 ) and Comparative Example 4 (90 mAh g -1 , 82mAh g -1 and 76mAh g -1 ).

[0088] Figure 4 The figure is a comparison of the long cycle stability of the composite materials prepared in Example 1 of the present invention and Comparative Examples 1, 2, 3, and 4 for use as positive electrode materials for sodium ion batteries. It can be clearly seen from the figure that the carbon-composite titanium / fluorine-doped composite sodium iron phosphate positive electrode material prepared in Example 1 has better cycle stability than the composite sodium ion battery negative electrode materials prepared in Comparative Examples 1, 2, 3, and 4. Example 1 achieved 90 mAh g after 5000 cycles at 10C. -1 The stable charging capacity of the battery is 91.3% of the initial cycle, which is superior to comparative examples 1, 2, 3, and 4 in terms of capacity retention rate and cycle stability.

[0089] The above properties indicate that the prepared multi-carbon composite titanium / fluorine dual-doped composite sodium iron phosphate cathode material has excellent rate performance and cycle performance, which can effectively inhibit the impurity phase NaFePO 4 The generation and regulation of material conductivity provides a new idea for the preparation of high-power, long-cycle, and high-capacity retention sodium-ion battery positive electrode materials, and can meet industrial needs in mass production.

[0090] For those skilled in the art, it is easy to improve and embellish the present invention without departing from the technology of the present invention, and these improvements and embellishments also fall within the scope of protection of the present invention. The present invention is not limited to the above-mentioned embodiments, and any changes within the claims of the present invention are covered within the scope of protection.

Claims

1. A carbon-composite titanium / fluorine dual-doped composite sodium iron phosphate composite material, characterized in that: The chemical formula of the carbon composite titanium / fluorine double-doped composite sodium iron phosphate is Na4Fe 3-2x Ti x (PO4) 2-y F 3y P2O7 / C, where 0 < x < 0.04 and 0 < y < 0.2; it has a hollow bowl-shaped porous structure.

2. The carbon-composite titanium / fluorine dual-doped composite sodium iron phosphate composite material according to claim 1, characterized in that: Carbon-composite titanium / fluorine dual-doped composite sodium iron phosphate composite material, carbon content is 1-5wt%; specific surface area is 5-15m 2 / g, and the pore size distribution range is 10-100nm.

3. The carbon-composite titanium / fluorine dual-doped composite sodium iron phosphate composite material according to claim 1, characterized in that: The particle size of the carbon-composite titanium / fluorine dual-doped composite sodium iron phosphate composite material is 0.2-10 μm.

4. The method for preparing the carbon-composite titanium / fluorine dual-doped composite sodium iron phosphate composite material according to claim 1, characterized in that: The steps include: S1. Prepare the raw material dispersion: according to the chemical stoichiometric formula Na4Fe 3-2x Ti x (PO4) 2-y F 3y P2O7 weigh the raw materials, and disperse the weighed carbon source, phosphorus source, sodium source, iron source, titanium source and fluorine source in water in proportion; S2, fineness of particles in the dispersion: the dispersion obtained in S1 is placed in a ball mill and a sand mill in turn to finen the raw material particles; S3, preparing a precursor material: spraying and granulating the dispersion obtained in S2 to obtain a composite sodium iron phosphate precursor material; S4, preparing a carbon-composite titanium / fluorine dual-doped composite sodium iron phosphate composite material: calcining the composite sodium iron phosphate precursor obtained in S3 at high temperature in a protective atmosphere, and crushing it to obtain the carbon-composite titanium / fluorine dual-doped composite sodium iron phosphate composite material.

5. The preparation method according to claim 4, characterized in that: The added amount of the carbon source is 5-15% of the theoretical NFPP product mass of the raw material.

6. The preparation method according to claim 4, characterized in that: The sodium salt is at least one of sodium carbonate, disodium bicarbonate, sodium dihydrogen carbonate, sodium pyrophosphate, sodium chloride, sodium nitrate, sodium sulfate, sodium thiosulfate, and sodium fluoride; the iron salt is at least one of ferrous sulfate heptahydrate, ferric nitrate nonahydrate, ferrocene, ferric sulfate, ferric phosphate, ferrous phosphate, ferric citrate, ferric oxalate, ferric chloride hexahydrate, and ferric acetylacetonate; the phosphorus source is at least one of phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate; and the carbon source is at least one of glucose, sucrose, polyvinyl pyrrolidone, citric acid, dopamine hydrochloride, and polyethylene glycol.

7. The preparation method according to claim 4, characterized in that: The titanium source is at least one of isopropyl titanate, tetraethyl titanate, tetrabutyl titanate, nano titanium oxide, titanium trichloride and titanium tetrafluoride; the fluorine source is at least one of ammonium fluoride, hydrofluoric acid and sodium fluoride.

8. The preparation method according to claim 4, characterized in that: In S3, the spray drying adopts an inlet air temperature of 150-230°C, an outlet air temperature of 80-120°C, a feed rate of 7-14 mL / min, and an inlet air pressure of 0.1-0.4 MPa.

9. The preparation method according to claim 4, characterized in that: The temperature used for high temperature calcination is 400-600°C and the time is 6-12h.

10. Use of the carbon-composite titanium / fluorine dual-doped composite sodium iron phosphate composite material according to any one of claims 1 to 3 or the carbon-composite titanium / fluorine dual-doped composite sodium iron phosphate composite material prepared by the preparation method according to any one of claims 4 to 9 in the positive electrode of a sodium ion battery.

Citation Information

Cited By

  • A high-rate type modified sodium ferric pyrophosphate material, a preparation method and application thereof

    CN122748597A